Relationship Between Self-Efficiency And Learning Interest With Student’s Learning Achievement - Munawaroh, Isti (Prosiding University Research Colloquium, 2021)
This study aims to determine the relationship between self-efficacy and interest in learning with student achievement. The research was conducted on students of SDN 1 Mranggen.This research is a type of correlational research. Research subjects were selected using purposive sampling technique. The samples taken were 71 high school students. The method of data collection was done by using a closed questionnaire. The instrument validity test was conducted using the product moment formula while the reliability test used the Cronbach alpha formula with the help of SPSS. The analysis prerequisite test consisted of normality test, multicollinearity test, heteroscedasticity test, autocorrelation test and linearity test. Data analysis used parametric statistical techniques, namely simple regression test and multiple regression test with the help of SPSS.The results showed that: (1) There was a relationship between self-efficacy and student achievement at SDN 1 Mranggen with the regression equation Y = 0.160x + 64.992, R2 of 0.599 and a significance of 35%. (2) There is a positive relationship between interest in learning and student achievement at SDN 1 Mranggen with the regression equation Y = 0.199x + 65.315, R2 of 0.576 and a significance of 33%. (3) There is a positive relationship between self-efficacy and interest in learning with student achievement at SDN 1 Mranggen with the regression equation Y = 0.102x1 + 0.098x2 + 63,152, R2 of 0.625 and a significance of 39%.